2008
DOI: 10.1094/phyto-98-9-0999
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Triazole-Based Fungicides for Fusarium Head Blight and Deoxynivalenol Control in Wheat: A Multivariate Meta-Analysis

Abstract: The effects of propiconazole, prothioconazole, tebuconazole, metconazole, and prothioconazole+tebuconazole (as a tank mix or a formulated premix) on the control of Fusarium head blight index (IND; field or plot-level disease severity) and deoxynivalenol (DON) in wheat were determined. A multivariate random-effects meta-analytical model was fitted to the log-transformed treatment means from over 100 uniform fungicide studies across 11 years and 14 states, and the mean log ratio (relative to the untreated check … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
227
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 284 publications
(244 citation statements)
references
References 32 publications
10
227
0
7
Order By: Relevance
“…For one major use of the Tool, predictions need to be made sufficiently early so that growers have time to optionally apply a fungicide. Fungicide application at anthesis provides the highest percent control (52). Applications during the milk stage may also be beneficial (72) but must adhere to pre-harvest interval regulatory requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For one major use of the Tool, predictions need to be made sufficiently early so that growers have time to optionally apply a fungicide. Fungicide application at anthesis provides the highest percent control (52). Applications during the milk stage may also be beneficial (72) but must adhere to pre-harvest interval regulatory requirements.…”
Section: Discussionmentioning
confidence: 99%
“…The models are simple, in that they contain a few easily calculated predictors, an asset when deploying models at the regional scale. The Risk Assessment Tool's purpose is to provide growers enough advanced notification, if the forecasted risk of an FHB epidemic is high, to optionally apply a fungicide at anthesis (51,52), an effective mitigation strategy, especially when combined with cultivar resistance (2,67,69).…”
mentioning
confidence: 99%
“…Fungicides of the demethylation inhibitors (DMIs) group, which includes triazoles, inhibit the C-14 α-demethylation of 24-methylenedihydrolanosterol, a precursor of ergosterol in fungi (Brent, 1995). Tebuconazole, metconazole and prothioconazole are among the azole fungicides with higher efficacy in suppressing FHB symptoms and reducing mycotoxin levels in mature grain (Paul et al, 2008).…”
mentioning
confidence: 99%
“…Currently, triazoles are the main fungicides used in FHB control in the major wheat producing countries (Paul et al, 2008;Becher et al, 2011).…”
mentioning
confidence: 99%
“…10,11) The sensitivity of the Fusarium graminearum species complex to metconazole and the efficacy of metconazole against isolates with different sensitivities have also been reported. 12) In field studies, optimal fungicide application timing for controlling FHB was shown to be different from that for controlling mycotoxin contamination.…”
Section: Introductionmentioning
confidence: 99%